Description of Ischemic Stroke Incident in the Intensive Care Room of Hospitals in Tanjungpinang City - Deliana, Muthia; Dewi Pusparianda; Rima Novia Putri (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2024)
Stroke is a non-communicable disease with the second highest incidence worldwide and the third leading cause of death. Globally, more than half are ischemic strokes. In Indonesia, especially Tanjungpinang City, the incidence of stroke is also increasing. Appropriate treatment needs to be carried out to prevent death and get a good prognosis. Results of field studies that have been carried out. A small number of ischemic strokes occur, but this number still results in quite high mortality and morbidity for patients. The aim of this study was to describe the incidence of stroke that occurred in the ICU Room at SE Hospital, Tanjungpinang City, Riau Islands. The method used is a retrospective study. Data collection was carried out using a Medical Record Study. The subjects of this research were all medical records of patients who had been treated in the ICU rooms of hospitals throughout Tanjungpinang City using purposive sampling. Research data processing was carried out using a simple approach. The results of this research showed that the majority were >50 years old, 39 samples (65%), 36 samples (60%) were male., length of stay less than 3 days as much as 55%, GCS entered the ICU at number 3-6 as much as 35%, had pressure 36 samples (60%) had high blood pressure, and all subjects had SpO2 in the range of 96-100 when they entered the hospital, 50 samples (83.3%) and the prognosis for leaving the ICU was death for 36 samples (60%). From this study it can be concluded that the patient's hemodynamic condition when first admitted to the ICU was unstable with a poor prognosis. It is hoped that after this research further research can be carried out in the form of surgical interventions that can stabilize the hemodynamics of ischemic stroke patients being treated in the ICU.